PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER BERBANTUAN FLIPBOOK TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 1 LEMBANG JAYA - Pratiwi, Natasya (Departemen Matematika, 2025)
One of the most important abilities to have when learning mathematics is the ability to understand mathematical ideas. However, in class XI of SMA Negeri 1 Lembang Jaya, this ability is still low. The proposed learning model to overcome this problem is the Numbered Heads Together (NHT) type cooperative learning model. Class XI of SMAN 1 Lembang Jaya is the focus of this research which aims to determine the relative advantages of NHT and direct learning models. This study used a quasi-experimental design with a non-equivalent control group with post-test only. Learners enrolled in the study were from classes XI F1 and XI F2 of SMAN 1 Lembang Jaya, which constituted the study population. Quizzes and tests with descriptive question formats were utilized as research tools, t-test was used to analyze the data, and the resulting P-value was 0.036. If the P-value < α = 0.05, then H0 is rejected. Class XI at SMAN 1 Lembang Jaya benefited more from using the NHT model than the direct learning model.Keywords– Flipbook, Cooperative Learning Model, Direct Learning Model, Numbered Heads Together, Mathematical Concept Understanding